Remote sensing and image interpretation - Lillesand, Thomas M (ohn Wiley & Sons, 2007)
Remote sensing is the science and art of obtaining information about an object, area, or phenomenon through the analysis of data acquired by a device that is not in contact with the object, area, or phenomenon under investigation. Providing an exciting introduction to the field, this book covers the science of remote sensing from physical basis to sensors and applications. The new Sixth Edition not only offers the latest information, but also has been revised to make the material more accessible.